Seroprevalence of Human Fascioliasis in Chaharmahal and Bakhtiyari Province, Southwestern Iran - Kouroush MANOUCHEHRI NAEINI; Farnaz MOHAMMAD NASIRI; Mohammad Bagher ROKNI; Soleiman KHEIRI (Tehran University of Medical Sciences, 2016)
Background: Fascioliasis caused by Fasciola hepatica and F. gigantica is a foodborne and waterborne zoonotic disease with a worldwide distribution. The illness occurs in regions with intensive sheep or cattle production. In some parts of Iran the incidence of human infection has increased over the past decades. Since Chaharmahal and Bakhtiyari Province has been known as a main pole of traditional animal husbandry and there was no information about human fascioliasis in this region, the present study was carried out on human population to determine the seroprevalence of this infection. Methods: In this cross-sectional study 1475 serum samples collected from individuals attended to clinical laboratory of the province were subjected to ELISA to detect anti-F. hepatica IgG antibodies. The socio- demographic characteristics of the subjects were also collected through questionnaires. Results: In spite of expectation, the present study showed that out of the 1475 serum samples examined anti- F. hepatica IgG antibodies were found only in two of the subjects (0.135%). Therefore, because of the very few number of positive cases no statistical analysis was applicable. Conclusion: According to the finding of this investigation, human fascioliasis may not be an important health problem in this region of Iran. However, for a better understanding of situation of this parasitic infection in this area more comprehensive animal and human studies are needed.